Chitosan-coated zein nanoparticles containing eugenol potentiates anesthesia in Nile tilapia - Ferreira, Andre L.; Charlie-Silva, Ives; Favero, Gisele C.; Silva de Melo, Nathalie F.; Fraceto, Leonardo F. [UNESP]; Junior, Jose Dias C.; Luz, Ronald K. (Elsevier B.V., 2020)
This study aimed to investigate the physical and chemical properties of mucoadhesive zein nanoparticles containing eugenol (NPZMA) and to evaluate their anesthetic effect in immersion baths, their stability in water and their effects on hemogasometric parameters of juvenile Oreochromis niloticus. Four experiments were performed: Experiment 1 characterized the nanoparticles. Experiment 2 evaluated the stability of NPZMA in water using an in vitro test with the following treatments: eugenol-80 mg L-1; NPZMA-80 mg L-1; NPZMA-40 mg L-1, NPZMA-20 mg L-1, water in natura and control (ethyl alcohol was added to the water at a proportion of 1:10 V/V). Experiment 3 tested the same treatments for time of anesthesia induction and recovery. Experiment 4 tested basal (group of non-anesthetized fish), eugenol-80 mg L-1 and NPZMA-40 mg L-1 for hemogasometric variables after two minutes of exposure. The new method for applying eugenol through mucoadhesive zein nanoparticles presented here exhibited positive loads and successful adherence to fish mucus. The method led to changes in water quality during the 60-min observation period, although it remained within the ideal range for O. niloticus. Experiment 3 revealed similar induction times for eugenol-80 mg L-1, NPZMA-80 mg L-1 and NPZMA-40 mg L-1 (P > .05). Recovery time was shortest for NPZMA-20 mg L-1 and longest for NPZMA-80 mg L-1 (P < .05). Experiment 4 found the concentrations tested to have no effects on hemogasometric variables (P > .05). The results demonstrate that mucoadhesive nanoparticles reduced the use of eugenol by 50%, as observed for NPZMA-40 mg L-1. Furthermore, this new form of eugenol application based on mucoadhesive zein nanoparticles showed good stability in water and did not alter hemogasometric parameters of juvenile O. niloticus.
Keywords: Clove oil; Handling stress; Hemogasometric; Induction and recovery; Oreochromis niloticus